Is endometrial thickness associated with fertility outcomes in intrauterine insemination? a cohort study - Du, Tong; Li, Wentao; Zhang, Suqun; Lyu, Qifeng; Kuang, Yanping; Mol, Ben W.; Wang, Yun; Mao, Xiaoyan; Zhao, Dong (Frontiers in Endocrinology, 2026)
BackgroundIntrauterine insemination (IUI) is the first line treatment for conditions such as unexplained or mild male factor infertility. Endometrial thickness (EMT) is an important indicator for predicting pregnancy outcomes in in-vitro fertilization. However, published data about whether EMT has a predictive capacity for success in IUI is controversial, and most studies suggest that endometrial thickness is not associated with IUI success, which limits its use in IUI.MethodsThis was a single center retrospective cohort study that included women undergoing IUI cycles from January 2007 to June 2021. We categorized EMT into thin (<7 mm), medium (7–14 mm), and thick (>14 mm) groups. For all IUI cycles, we computed adjusted odds ratios (aORs) and 95% confidence intervals (CIs) using Generalized Estimating Equation Regression Models. For first IUI cycles specifically, we applied both Inverse Propensity Score Weighted Regression Adjustment Models and Propensity Score Matching Analyses to compare fertility outcomes. Moreover, we computed the predicted probability of primary outcomes for continuous EMT in mm using restricted cubic splines, allowing for non-linear relationships.ResultsThis cohort included 13103 IUI cycles involving 7609 women. Across all cycles, live birth rates were lower in the thin EMT group (11.0%) and higher in the thick EMT group (16.9%), compared to the medium EMT group (13.5%)—aOR 0.82 (95% CI 0.67-0.998) for thin EMT and aOR 1.22 (95% CI 1.02-1.45) for thick EMT. The results were consistent when analyzing first cycles only. Restricted cubic spline analysis revealed a linear positive gradient that suggests a progressive increase in live birth rates with increasing EMT.ConclusionsIn natural or Letrozole with or without Human Menopausal Gonadotropin stimulated IUI cycles, EMT on trigger day is a significant predictor of live birth, with thin EMT associated with reduced success rates. EMT measurements could serve as a useful marker in IUI treatment.